Energy Sufficiency Kaizen Achieving Zero Energy Cost and Variance with Sufficiency-inclu- sive Private Energy Portfolios - Overturf, Michael C.; Chrosny, Wojciech M.; Stine, Richard G. (Distributed Generation & Alternative Energy Journal, 2011)
Mid-sized industrial and commercial firms consume between 300 to 30,000 MWh of electrical and thermal energy per month. Energy man- agers in these firms seek to minimize costs, both in terms of absolute expense and the indirect costs of variances from expected quality. While many business managers negotiate direct utility costs, few firms have a continuous improvement process that structure cost con- trol, efficiency improvement, and risk reduction. A complete manage- ment process requires planning, quantifying and exercising options, and variance analysis of efficiency and risk measures. The methods to ac- complish this are not well understood. We describe how an Energy Index is used in the context of the Deming cycle with sufficiency-inclusive private energy portfolios, usu- ally implemented as a microgrid. We discuss valuation, planning tech- niques, and show how business can institute a process that can be used to drive both energy cost and variance to zero over time.